Altruism, Environmental Concerns, and Pro-environmental Behaviors of Urban Residents: A Case Study in a Typical Chinese City - Xu, Ying; Li, Wanxin; Chi, Shangxin (Frontiers in Psychology, 2021)
To investigate the relationships between altruism, environmental concerns, and ordinary people’s pro-environmental behaviors that go beyond self-interested NIMBY-ism, we examined measurements of altruism and environmental concerns in a Chinese context and developed a scale that measured people’s pro-environmental behaviors at the individual, organizational, and policy level. We then conducted a tailor-made, face-to-face survey (N=603) and found, first, that old age, gender (being a woman), party affiliation, and education level are positively associated with pro-environmental behaviors at the individual, organizational, and policy levels. We next found that human domination worldviews are negatively associated with individual- and organizational-level pro-environmental behaviors and that eco-centric worldviews are positively associated with individual-level pro-environmental behaviors. Third, we found that altruistic behaviors (prosocial behaviors and/or donations) are positively associated with pro-environmental behaviors. In short, awareness of the ecological crisis and altruism can stimulate people’s pro-environmental behaviors in China. Meanwhile, it is doubtful that people care more for the environment after their living standards have improved, because socioeconomic status indicators are not statistically significant for individual-level pro-environmental behaviors.